National culture: tradition and innovation (Journal of Philosophy Culture and Political Science, 2019)
This article discusses the concept of tradition and innovation in the national culture. This concept has long been a center for the study of many scientists and philosophers. The concept of tradition and innovation are correlated with different layers of human culture and human history. Interaction in the culture of the people of old and new, and borrowed by a number of ways: simple penetration of the elements of one culture to another, the synthesis and use of borrowings in accordance with traditional norms and customs. We also consider the traditional culture of the Kazakh people, which is characterized by a high continuity in the moral education of the younger generation, the spiritual perfection of the individual.